Peran Guru Penggerak dalam meningkatkan kompetensi pedagogik guru non penggerak di SMA Negeri 5 Barru - Irawana, Wiwi; Arismunandar; Irmawati (Irfani, 2026)
This study investigates the role of Guru Penggerak (Teacher Mobilizers) in enhancing the pedagogical competence of non-Guru Penggerak teachers at SMA Negeri 5 Barru, Indonesia. Employing a descriptive qualitative approach, data were collected through in-depth interviews and documentation involving the principal, Guru Penggerak, non-Guru Penggerak teachers, and students. The findings indicate that Guru Penggerak contribute significantly to pedagogical improvement through three main roles: (1) facilitating professional learning communities via internal training, workshops, regular discussions, and sharing best practices; (2) serving as model practitioners by demonstrating differentiated instruction, technology integration, and contextual curriculum development; and (3) fostering collaborative spaces for peer dialogue, reflective practice, and problem-solving. These roles promote improved mastery of learning theories, curriculum design, ICT utilization, and empathetic communication among non-Guru Penggerak teachers. Supporting factors include principal leadership, a collaborative school culture, and teacher motivation. Challenges identified include limited time, uneven ICT access, and varied teacher readiness. Overall, Guru Penggerak act as key agents of educational transformation by sustainably strengthening teaching quality and professional capacity within the school context.